Neuroleadership as an Asset in Educational Settings: An Overview - Evgenia Gkintoni; Constantinos Halkiopoulos; Hera Antonopoulou (Emerging Science Journal, 2022)
Objectives: The goal of this research is to investigate the scientific basis for integrating neuroscience in general, and cognitive neuroscience in particular, into the field of educational leadership. In recent decades, the scientific community has shown a great interest in integrating neuroscience into higher education and the many levels of leadership education and decision-making that are crucial to a range of educational difficulties that leadership leaders are called upon to handle. Methods/Analysis: The present effort involves a systematic review of research publications published in the preceding two decades after a keyword search of reputable international databases. This review incorporates papers from Scopus, PubMed, Elsevier, and PsycINFO databases. The terms neuroleadership and education were used in combination with the four subfields outlined in the research: Among them are decision-making and problem-solving abilities, emotional control, cooperation and influence with others, and facilitation of change. Findings: The review's results underscore the vital relevance of neuroscience integration into educational leadership difficulties and highlight ethical concerns regarding its deployment in educational settings. Novelty /Improvement: The novelty of this work is that it conducted a review of the literature on neuroleadership using a combination of executive function parameters, more precisely cognitive flexibility, decision-making, problem-solving, emotional regulation, the mirror neuron system, and behavioral data from studies conducted in educational and administrative settings. Doi: 10.28991/ESJ-2022-06-04-016 Full Text: PDF